Spontaneous low-protein intake in older CKD patients: one diet may not fit all - Vettoretti, Simone; Molinari, Paolo; Armelloni, Silvia; Castellano, Giuseppe; Caldiroli, Lara (Frontiers in Nutrition, 2024)
Background Protein restriction has been extended to stage 3 chronic kidney disease (CKD) regardless of age in the latest K-DOQI guidelines for the dietary management of patients with CKD. However, in elderly CKD patients there is a tendency to a spontaneous reduction in protein and energy intake that may impair the overall nutritional status. The aim of our study is to assess whether there are differences in malnutrition, exercise capacity and inflammatory status in elderly CKD patients with spontaneously low protein intake (sLPI) compared with patients with normal protein intake (NPI). Methods We performed a cross-sectional analysis of 123 incident patients. Malnutrition was assessed using Malnutrition Inflammation Score (MIS) and serum markers; As for physical performance, we used Short Physical Performance Battery (SPPB) and handgrip strength. Results We found that in older patients with advanced CKD, as many as 68% had low spontaneous protein intake, and they were more malnourished evaluated with MIS (25% vs. 10%, p = 0.033), protein-energy wasting (PEW) (43% vs. 14%, p = 0.002) and nPCR (0.63[0.51–0.69] vs. 0.95[0.87–1.1], p < 0.0001). They also had worse body composition, in terms of lower mid-arm muscular circumference (MAMC), fat tissue index (FTI) and higher overhydration (OH). sLPI patients also had higher levels of IL6 (4.6[2.9–8.9] vs. 2.8[0.8–5.1], p = 0.002). Moreover, sLPI patients were frailer (33% vs. 24%, p = 0.037) and had poorer physical performance especially when assessed with (SPPB) (7[5–9] vs. 9[7–10], p = 0.004) and gait test time (6.08 + 2 vs. 7.22 + 2.7, p = 0.04). sLPI was associated with lower physical performance [SPPB OR, 0.79 (0.46–0.97), p = 0.046] and malnutrition [MIS 1.6 (1.05–3.5), p = 0.041] independently from patients’ age and eGFR. Conclusion We found that in older patients with advanced CKD, up to 68% had low spontaneous protein intake and were frailer, more malnourished and with lower physical performance. These findings emphasize the importance of assessing patients’ needs, and personalized approaches with individual risk–benefit assessments should be sought. To achieve the best possible outcomes, targeted interventions should use all available tools.